We Love Mr King : Malay Muslims of Southern Thailand in the Wake of the Unrest - Anusorn Unno (ISEAS Publishing, 2019)
This book is an ethnography of the Malay Muslims of Guba, a pseudonymous village in Thailand’s Deep South, in the wake of the unrest that was primarily reinvigorated in 2004. It argues that the unrest is the effect of the way in which different forms of sovereignty converge around the residents of this region and the residents at the same time have cultivated themselves and obtained and enacted agency through the sovereigns. Rather than asking why the violence is increasing and who is behind it, like most scholarly works on the topic, it examines how different forms of sovereignty — ranging from the Thai state and the monarchy to Islamic religious movements, the insurgents and local strongmen — impose subjectivities on the residents, how they have converged in so doing and what tensions have followed, and how the residents have dealt with these tensions and cultivated themselves and obtained and enacted agency through the sovereigns. The phrase “We Love Mr King” or rao rak nay luang inscribed on the decorated, footed tray is one example of how the residents crafted themselves as royal subjects and enacted agency through the sovereign monarch